FEATURES OF ANXIETY–DEPRESSIVE DISORDERS IN PARKINSON’S DISEASE (International journal of medical sciences, 2025)
This article examines the prevalence and characteristics of anxiety and depressive disorders in Parkinson’s disease. During the study, patients’ psychological status was assessed using the Beck Depression Inventory and the Sheehan Anxiety Scale. The findings show that psychological disturbances—particularly depression and anxiety—are widespread among individuals with Parkinson’s disease. These disorders adversely affect quality of life and are important to identify early for timely treatment.